A peer support program results in greater health benefits for peer leaders than other participants: evidence from the Kerala diabetes prevention program - Tilahun Haregu; Zahra Aziz; Yingting Cao; Thirunavukkarasu Sathish; Kavumpurathu Raman Thankappan; Jeemon Panniyammakal; Pilvikki Absetz; Elezebeth Mathews; Sajitha Balachandran; Edwin B. Fisher; Brian Oldenburg (BMC, 2023)
Abstract Background Peer support programs are promising approaches to diabetes prevention. However, there is still limited evidence on the health benefits of peer support programs for lay peer leaders. Purpose To examine whether a peer support program designed for diabetes prevention resulted in greater improvements in health behaviors and outcomes for peer leaders as compared to other participants. Methods 51 lay peer leaders and 437 participants from the Kerala Diabetes Prevention Program were included. Data were collected at baseline, 12 months, and 24 months. We compared behavioral, clinical, biochemical, and health-related quality of life parameters between peer leaders and their peers at the three time-points. Results After 12 months, peer leaders showed significant improvements in leisure time physical activity (+ 17.7% vs. + 3.4%, P = 0.001) and health-related quality of life (0.0 vs. + 0.1, P = 0.004); and a significant reduction in alcohol use (-13.6% vs. -6.6%, P = 0.012) and 2-hour plasma glucose (-4.1 vs. + 9.9, P = 0.006), as compared to participants. After 24 months, relative to baseline, peer leaders had significant improvements in fruit and vegetable intake (+ 34.5% vs. + 26.5%, P = 0.017) and leisure time physical activity (+ 7.9% vs. -0.9%, P = 0.009); and a greater reduction in alcohol use (-13.6% vs. -4.9%, P = 0.008), and waist-to-hip ratio (-0.04 vs. -0.02, P = 0.014), as compared to participants. However, only the changes in fruit and vegetable intake and waist-to-hip ratio were maintained between 12 and 24 months. Conclusion Being a peer leader in a diabetes prevention program was associated with greater health benefits during and after the intervention period. Further studies are needed to examine the long-term sustainability of these benefits.